Analisis Sitem Informasi Akuntansi Penggajian Untuk Meningkatkan Efektifitas Pengendalian Internal Pada Lldikti Wilayah I Sumut - Dinda Anggi Nurhayati; Juliana Nasutiona (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2022)
The study aims to analyze the payroll accounting information system that has been implemented by LLDIKTI WIL I SUMUT and also to analyze the payroll accounting information system on the eggectiveness of internal control. The type of research conducted is descriptive research, which focuses on payroll accounting information system at LLDIKTI WIL I SUMUT and internal control systems at LLDIKTI WIL I SUMUT. The method used in this research is documentation. The results of the study found evidence that the Accounting Departmen was syill responsible for paying employee salaries. A healthy practice that is applied to support the effectiveness of internal control is that the basic salary of employees is paid by transferring the basic salary to each employee’s eccount by the director and the salary slip is made in duplicate.